Investigation of fuel cells through experiments - Noralyza Che Mansor
This paper presents the investigation in fuel cells through experiments. The aim of this project is to investigate the use of renewable energy in the world today and more specifically, to do investigation in fuel cells characteristic as the renewable energy using 'Hydro Genius Teach' experiment set.